Efektivitas Pendidikan Seksual Dalam Meminimalisir Perilaku Seksual Pranikah Pada Remaja Ditinjau Dari Jenis Kelamin Dan Lokasi Sekolah - Prita Yulia Maharani; Suroso Suroso; Tatik Meiyuntariningsih (Universitas Muhammadiyah Jember, 2019)
Lack of knowledge about education and information about sex makes young people vulnerable to accessing information about pornography, easily affected by the environment and premarital sexual intercourse which is higher for teenage boys compared to girls. The purpose of this study is to see whether sexual education is effective in minimizing premarital sexual behavior in adolescents in terms of gender and school location. The subjects of this study were high school students in Surabaya. Test analysis in this study using Test T. The results of the calculation of hypothesis 1 indicate that sexual education training has effectiveness in minimizing sexual behavior. Hypothesis 2 shows that premarital sexual behavior in male students is higher than female students after being given sexual education. Hypothesis 3 shows that the distant location of schools with localization of premarital sexual behavior is higher than the location of schools that are close to localization after being given sexual education. the implications of this research can be used as a reference for the school in order to minimize sexual behavior.